Mechanisms of Macrophage Polarization in Insulin Signaling and Sensitivity - Orliaguet, Lucie; Dalmas, Elise; Drareni, Karima; Venteclef, Nicolas; Alzaid, Fawaz (Frontiers in Endocrinology, 2020)
Type-2 diabetes (T2D) is a disease of two aetiologies: metabolic and inflammatory. At the cross-section of these aetiologies lays the phenomenon of metabolic inflammation. Whilst metabolic inflammation is characterised as systemic, a common starting point is the tissue-resident macro-phage, who’s successful physiological or aberrant pathological adaptation to its microenvironment determines disease course and severity. This review will highlight the key mechanisms in macrophage polarisation, inflammatory and non-inflammatory signalling that dictates the development and progression of insulin resistance and T2D. We first describe the known homeostatic functions of tissue macrophages in insulin secreting and major insulin sensitive tissues. Importantly we highlight the known mechanisms of aberrant macrophage activation in these tissues and the ways in which this leads to impairment of insulin sensitivity/secretion and the development of T2D. We next describe the cellular mechanisms that are known to dictate macrophage polarisation. We review recent progress in macrophage bio-energetics, an emerging field of research that places cellular metabolism at the centre of immune effector function. Importantly, following the advent of the metabolically-activated macrophage, we cover the known transcriptional and epigenetic factors that canonically and non-canonically dictate macrophage differentiation and inflammatory polarisation. In closing perspectives, we discuss emerging research themes and highlight novel non-inflammatory or non-immune roles that tissue macrophages have in maintaining microenvironmental and systemic homeostasis.